2019
DOI: 10.1140/epjp/i2019-13024-2
|View full text |Cite
|
Sign up to set email alerts
|

Mortar analysis of historic buildings damaged by recent earthquakes in Italy

Abstract: The paper presents an experimental study on mortar samples taken from historic and monumental buildings damaged or collapsed following the seismic events in Central Italy (2016-2017). Sixty-one samples were analysed with a set of diagnostic investigations to characterize the mortar and correlate it with the performance of the masonry. The techniques used were: X-Ray diffraction, scanning electron microscopy and microanalysis, differential scanning calorimetry, calcimetry, Fourier-transform infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Cyclic direct shear tests performed on the fraction of non-cohesive mortar samples with particle-size less than or equal to 2 mm, carried out at different normal-stress levels, provide an average friction coefficient equal to 0.9 and a cohesion equal to 0.025 MPa. 28 The mortar used for the construction of the wall was prepared according to the defined mix design, specimens were sampled during construction and tested according to EN 1015-11 the day before the shake table experiments. The samples collected have unit weight w m = 16.9 kN/m 3 (CV = 3.3%, six tests), compressive strength f m = 0.87 MPa (CV = 55.9%, 10 tests) and flexural tensile strength f mf = 0.36 MPa (CV = 49.9%, four tests).…”
Section: Mechanical Characterisation Of Construction Materialsmentioning
confidence: 99%
“…Cyclic direct shear tests performed on the fraction of non-cohesive mortar samples with particle-size less than or equal to 2 mm, carried out at different normal-stress levels, provide an average friction coefficient equal to 0.9 and a cohesion equal to 0.025 MPa. 28 The mortar used for the construction of the wall was prepared according to the defined mix design, specimens were sampled during construction and tested according to EN 1015-11 the day before the shake table experiments. The samples collected have unit weight w m = 16.9 kN/m 3 (CV = 3.3%, six tests), compressive strength f m = 0.87 MPa (CV = 55.9%, 10 tests) and flexural tensile strength f mf = 0.36 MPa (CV = 49.9%, four tests).…”
Section: Mechanical Characterisation Of Construction Materialsmentioning
confidence: 99%
“…In 1794-1797 sand transportation cost was the 5% of the cost of raw building, or a sixth of the cost of workforce 9 . Recent studies on mortars (Roselli, 2019) from four different locations confirm the difficulties in supplying good building materials. The lime sands were too fines and are one of the causes behind masonry disintegration.…”
Section: Exchanges Of Local Skills and Resourcesmentioning
confidence: 89%
“…In the ordinary buildings of Central Italy, in the aftermath of the earthquakes, different levels of unit and mortar quality were detected and it was confirmed that the use of undressed stone units, in conjunction with low-strength mortar, often led to poor earthquake response (Liberatore et al 2016). Dramatically low levels of lime were measured in mortars collected in the Amatrice area from damaged buildings, with the same mortar type being used both in the external leaves joints and in the internal core of the walls (Mirabile Gattia et al 2019;Roselli et al 2019). Churches usually present a higher masonry quality in comparison to ordinary buildings, but differences need to be recognized between main historical centers and small settlements.…”
Section: Characteristics Of the Churchesmentioning
confidence: 95%